A Magnetic‐Field Guided Interface Coassembly Approach to Magnetic Mesoporous Silica Nanochains for Osteoclast‐Targeted Inhibition and Heterogeneous Nanocatalysis. Issue 25 (7th May 2018) - Wan, Li; Song, Hongyuan; Chen, Xiao; Zhang, Yu; Yue, Qin; Pan, Panpan; Su, Jiacan; Elzatahry, Ahmed A.; Deng, Yonghui
Abstract: 1D core–shell magnetic materials with mesopores in shell are highly desired for biocatalysis, magnetic bioseparation, and bioenrichment and biosensing because of their unique microstructure and morphology. In this study, 1D magnetic mesoporous silica nanochains (Fe3 O4 @nSiO2 @mSiO2 nanochain, Magn‐MSNCs named as FDUcs‐17C) are facilely synthesized via a novel magnetic‐field‐guided interface coassembly approach in two steps. Fe3 O4 particles are coated with nonporous silica in a magnetic field to form 1D Fe3 O4 @nSiO2 nanochains. A further interface coassembly of cetyltrimethylammonium bromide and silica source in water/ n ‐hexane biliquid system leads to 1D Magn‐MSNCs with core–shell–shell structure, uniform diameter (≈310 nm), large and perpendicular mesopores (7.3 nm), high surface area (317 m 2 g −1 ), and high magnetization (34.9 emu g −1 ). Under a rotating magnetic field, the nanochains with loaded zoledronate (a medication for treating bone diseases) in the mesopores, show an interesting suppression effect of osteoclasts differentiation, due to their 1D nanostructure that provides a shearing force in dynamic magnetic field to induce sufficient and effective reactions in cells. Moreover, by loading Au nanoparticles in the mesopores, the 1D Fe3 O4 @nSiO2 @mSiO2 ‐Au nanochains can service as a catalytically active magnetic nanostirrer for hydrogenation of 4‐nitrophenol with high catalytic performance and good magnetic recyclability. Abstract : 1D magnetic mesoporous silica nanochains with core–shell structure, large radial mesopores, and high surface area, are synthesized through a magnetic‐field‐guided interface coassembly approach. By using their fast magnetic responsiveness and large pores for loading zoledronate or Au nanoparticles, the composites exhibit favorable inhibition to osteoclasts differentiation under a dynamic magnetic field and behave as high‐performance heterogeneous nanocatalysts.